2017
DOI: 10.3390/molecules22101720
|View full text |Cite
|
Sign up to set email alerts
|

Stereopermutation on the Putative Structure of the Marine Natural Product Mucosin

Abstract: A stereodivergent total synthesis has been executed based on the plausibly misassigned structure of the unusual marine hydrindane mucosin (1). The topological connectivity of the four contiguous all-carbon stereocenters has been examined by selective permutation on the highlighted core. Thus, capitalizing on an unprecedented stereofacial preference of the cis-fused bicycle[4.3.0]non-3-ene system when a Michael acceptor motif is incorporated, copper-mediated conjugate addition furnished a single diastereomer. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 104 publications
(121 reference statements)
0
18
0
Order By: Relevance
“…Compounds that have been synthesised include ancorinoside A, 487 diacarnoxide C, 488 and plakinidone C. 406 The structures of gracilioether I and mucosin have been disproven by synthesis but no alternatives have been proposed. 489,490 Jaspisin, isojaspisin and (Z)narain have been synthesised, 491 as have smenothiazoles A 406,492 and B. 492 The peptides ciliatamides A and D (revised to 1212 and 1213 respectively), 493 euryjanicin E, 494 reniochalistatin E, 495 and theonellapeptolide Id 496 and the diaryl ether tedarene A have all been synthesised.…”
Section: Spongesmentioning
confidence: 99%
“…Compounds that have been synthesised include ancorinoside A, 487 diacarnoxide C, 488 and plakinidone C. 406 The structures of gracilioether I and mucosin have been disproven by synthesis but no alternatives have been proposed. 489,490 Jaspisin, isojaspisin and (Z)narain have been synthesised, 491 as have smenothiazoles A 406,492 and B. 492 The peptides ciliatamides A and D (revised to 1212 and 1213 respectively), 493 euryjanicin E, 494 reniochalistatin E, 495 and theonellapeptolide Id 496 and the diaryl ether tedarene A have all been synthesised.…”
Section: Spongesmentioning
confidence: 99%
“…Early on in our synthetic campaign directed toward the preparation of (−)-mucosin we voiced some concerns about the geometry at the points of fusion. , Assuming that arachidonic acid ( 3 ) is indeed the biogenetic progenitor, the core structure found in 1 invokes a formal disrotatory ring closure. A survey of the known enzymes operating on this particular polyene system singled out 5-lipoxygenase (5-LOX) as a possible asymmetric promotor, catalyzing stereospecific peroxidation at C5 and the concomitant formation of a 6 E ,8 Z -diene system .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our previous efforts, , we devised a flexible strategy that evolved around the application of a diastereoselective conjugate addition (Scheme ). Relying on a known Diels–Alder protocol to furnish the asymmetric starting point, the featured Michael acceptor 10 would be obtainable from the corresponding en route β-keto ester 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, irrespective of how the analogy is reached, the fundamental aspects related above make these natural products interesting investigative targets. The authors of the present paper have been engaged in a successful campaign that ultimately established the correct structure of the marine eicosanoid (−)-mucosin ( 1 ) by stereocontrolled total synthesis [50,51,52]. In contrast to the claimed cis -fused structure 4 , it was clearly demonstrated that the natural product has the trans -fused structure 6 (Figure 2).…”
Section: Introductionmentioning
confidence: 90%